2021
DOI: 10.1200/jco.2021.39.3_suppl.201
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative FLOT plus anti-PD-L1 avelumab (FLOT-A) in resectable oesophagogastric adenocarcinoma (OGA): Interim safety analysis results from the ICONIC trial.

Abstract: 201 Background: ICONIC is a single-arm phase II trial investigating the safety and efficacy of perioperative FLOT-A in resectable OGA. Following a 3+3 design safety run-in phase, standard dose FLOT with 10mg/kg IV avelumab (dose level 0) q2weeks was taken forward into the main study. The aims of this pre-planned interim analysis were to assess perioperative safety and R0 resection rates. Methods: The interim analysis occurred once the 15th patient treated at dose level 0 reached 30 days post-surgery. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The geographic distribution of included studies is shown in eFigure 1 in the Supplement. non-RCTs, and 25 of them were single-group 21,22,[24][25][26][27]30,31,[33][34][35][36][37][39][40][41][42][43][44][45][46][47] and 2 were dual-group trials. 28,29 Twenty-three trials 21,23,24,[27][28][29][31][32][33][34][35][36][37][38][39][42][43][44]46,47 enrolled patients with ESCC and applied anti-PD-1 antibody.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geographic distribution of included studies is shown in eFigure 1 in the Supplement. non-RCTs, and 25 of them were single-group 21,22,[24][25][26][27]30,31,[33][34][35][36][37][39][40][41][42][43][44][45][46][47] and 2 were dual-group trials. 28,29 Twenty-three trials 21,23,24,[27][28][29][31][32][33][34][35][36][37][38][39][42][43][44]46,47 enrolled patients with ESCC and applied anti-PD-1 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, based on 17 trials, 23,25,27,30,[33][34][35][36][37][38][39][40][41][42][43]46,47 the pooled MPR rate was 48.9% (95% CI, 42.0%-55.9%), with mild heterogeneity (I 2 = 50.3%; 95% CI, 13.1%-71.5%; P = .10) (Figure 3). In terms of safety, 14 trials, 23,26,27,29,32,34,36,38,40,42,[44][45][46]48 23,[27][28][29]31,[33][34][35][37][38][39][40][41][42]44,[46][47][48] was 98.6% (95% CI, 97.1%-99.6%), with no evidence of significant heterogeneity (eFigure 9 in the Supplement).…”
Section: Clinical and Safety Outcomesmentioning
confidence: 99%
“…Our observations appear consistent with other small prospective trials reported to date in which ICIs have been incorporated into perioperative chemotherapy for molecularly unselected patients with GC. [32][33][34] Ongoing phase III trials randomizing patients with GC receiving perioperative chemotherapy to the addition of an ICI or placebo may validate acceptable toxicities. 35,36 Despite the dramatic responses to ICIs demonstrated in MSI-H tumors, the adoption of MSI/dMMR testing in the clinical setting remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase 2 study in (20). Atezolizumab and avelumab are also being studied in combination with FLOT in the DANTE (NCT03421288) and ICONIC (NCT03399071) trials (21,22). Finally, KEYNOTE-585 is an active phase 3 trial that will establish the OS, event-free survival (EFS) and pCR rate of neoadjuvant and adjuvant pembrolizumab plus chemotherapy (cisplatin + 5-FU before and after surgery) versus placebo plus chemotherapy in patients with advanced (T3/T4 or node positive) gastric or GEJ adenocarcinoma (23).…”
Section: Gastric Cancermentioning
confidence: 99%